Mechanisms of self-resistance in the platensimycin and platencin producing Streptomyces platensis MA7327 and MA7339 strains - Peterson, Ryan M. (2014)
Platensimycin (PTM) and platencin (PTN) are potent inhibitors of bacterial fatty acid synthases and have emerged as promising antibacterial drug leads. We previously characterized the PTM and PTN biosynthetic machineries in the Streptomyces platensis producers. We now identify two mechanisms for PTM and PTN resistance in the S. platensis producers - the ptmP3 or ptnP3 gene within the PTM-PTN or PTN biosynthetic cluster and the fabF gene within the fatty acid synthase locus. PtmP3/PtnP3 and FabF confer PTM and PTN resistance by target replacement and target modification, respectively. PtmP3/PtnP3 also represents an unprecedented mechanism for fatty acid biosynthesis in which FabH and FabF are functionally replaced by a single condensing enzyme. These findings challenge the current paradigm for fatty acid biosynthesis and should be considered in future development of effective therapeutics targeting fatty acid synthase.